Coffee intake and risk of diabetic nephropathy: a Mendelian randomization study - Fang, Jiaxi; Song, Kai; Zhang, Di; Liang, Yan; Zhao, Huan; Jin, Juan; He, Qiang (Frontiers in Endocrinology, 2023)
Rationale and objective A causal relationship concerning coffee intake and diabetic nephropathy (DN) is controversial. We conducted a Mendelian randomization study to assess the causal nature of these associations. Methods 40 independent single nucleotide polymorphisms (SNPs) associated with coffee intake were selected from the UK Biobank study. Summary-level data for diabetic nephropathy were obtained from publicly available genome-wide association studies (GWAS) and the FinnGen consortium. Inverse variance weighted (IVW), MR-Egger, and weighted median (WM) methods were used to examine a causal association. Sensitivity analyses included Cochran’s Q test, the intercept of MR-Egger, MR-PRESSO, and the Outlier method. Leave-One-Out sensitivity analyses were also conducted to reduce the heterogeneity. Results Our current study demonstrated positive associations of genetically predicted coffee intake with diabetic nephropathy (OR=1.939; P = 0.045 and type 2 diabetes with renal complications (OR = 2.787, P= 0.047). These findings were robust across several sensitivity analyses. Conclusions This study found a positive correlation between coffee consumption and the risk of diabetic nephropathy using genetic data. For a more accurate and trustworthy conclusion, subgroup analysis on coffee intake, including preparing method, variety of coffee, and quantity, is required.